Examining the Synthesis of Islamic Commercial Principles and Local Customary Practices: A Case Study of Nyambut Sawah Traditions in Tejamari, Banten - Jamaluddin Jamaluddin; Milatul Hayat; Masduki Masduki; Oom Mukarromah; Jamaludin Jamaludin (Journal of Islamic Law)
The influence stemming from the intersection of local traditions and religious percept manifests itself in the practice of nyambut sawah (paddy cultivation) among the Tejamari community. This practise resembles the utilisation of agricultural land (muzāra’ah) in Islamic commercial law (fiqh mu’āmalah), wherein landowners provide agricultural land to cultivators for cultivation with a profit-sharing system. This article aims to analyse the extent to which the practice of nyambut sawah adopts the principles of Islamic commercial law. This study employs a normative-empirical approach, conducting observations and interviews with eighteen informants. The research finds that the nyambut sawah tradition practiced by the Tejamari community reflects the muzāra’ah contract in fiqh mu’āmalah. The muzāra’ah contract is reflected in five models of profit-sharing systems, wherein the division of tasks, responsibilities, profits, and risks has been mutually agreed upon. Despite differences in opinion regarding the responsibility for the cost of rice milling (ngeprik padi), this practice still maintains values of mutual assistance between landowners and cultivators in overcoming economic difficulties. This article argues that local traditions and religious values can together provide solutions for the sustainability of agricultural activities.